2014
DOI: 10.1016/j.electacta.2013.08.186
|View full text |Cite
|
Sign up to set email alerts
|

Tribo-electrochemical impedance: A new technique for mechanistic study in tribocorrosion

Abstract: On the basis of a classical model of triboelectrochemistry, a new approach is proposed based on an impedance ratio of a mechanical perturbation and of an electrochemical response. Theoretical derivation, experimental setup and application to a passive stainless steel in a borate solution are presented. Transient characteristics yielded by the technique, associated to a permanent tribological regime, are found to obey a two-time-constant law. They are discussed and compared to the global repassivation transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Where v is the constant velocity of the abrading body, x the position variable, and w the width of the abraded track. It should be mentioned that the more general case of a time dependent velocity has been dealt with in [8].…”
Section: General Properties Of the Formal DC And Ac Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Where v is the constant velocity of the abrading body, x the position variable, and w the width of the abraded track. It should be mentioned that the more general case of a time dependent velocity has been dealt with in [8].…”
Section: General Properties Of the Formal DC And Ac Responsesmentioning
confidence: 99%
“…The electrochemical response is ascribed to the recovery of the surface conditions by several simultaneous processes including build-up of the double layer, growth of a new surface film, dissolution of the transitory unprotected metal… The main goal is to better understand the reciprocal or synergetic interaction between mechanical and reactive contributions to the overall tribocorrosion process. Most of the works in the field have remained restricted to steady state (current to voltage curves) [1][2][3][4][5][6] or transient techniques [5,7,8] aimed at separating the individual contributions of the film growth and that of the metal dissolution to the total wear. Most powerful techniques in the field of electrochemical corrosion mechanism and particularly complex electrochemical impedance spectroscopy in a wide frequency range, EIS, have been very scarcely used [5]; but no electrochemical model addressing the ac response of a transient current being available, they remained at a strictly descriptive level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs [15,[30][31][32][33]. It was shown that in a two-body abrasioncorrosion contact (reciprocating or pin-on-disc) where an inert counterface slides on a passive metal, the depassivated area is generated at a rate that depends on the sliding velocity, , and the applied normal force, .…”
Section: Introductionmentioning
confidence: 99%
“…The application of potentiostatic and potentiodynamic polarization in tribocorrosion studies, although not standardized, has been well documented [3,5]. In contrast, the use of methods such as electrochemical impedance spectroscopy (EIS) and electrochemical noise (EN), the latter especially promising in shedding light on the tribocorrosion of multiphase alloys, has not been formalized yet [16][17][18][19]. Also, well-researched tribo-electrochemical techniques able to measure in situ localized phenomena are lacking [11].…”
Section: Introductionmentioning
confidence: 99%